Thai Cultural Dance with Ruesi Dadton (traditional Thai exercise): The Effects on Physical Health, Cognitive Performance, and Quality of Life in Older Adults - Thiantongin, Pitchanan; Khanthong, Phaksachiphon; Janjang, Siriwan; Namboonlue, Chaiyawat; Thaotho, Savitree; Suksai, Surasak (Physical Education Theory and Methodology, 2025)
Background. Regular physical activity offers substantial benefits for older adults. However, it must be varied and engaging to sustain their participation. Lampleon Ruesi Dadton (LRD), a form of Thai cultural dance, has been developed as an integrated exercise program specifically tailored for older adults. Objectives. This pilot study aimed to investigate the effects of LRD on physical health, cognitive performance, and quality of life (QoL) among eleven older adult women. Materials and Methods. Participants attended 20-minute LRD dance sessions three times per week for four weeks. The assessment of physical health, cognition, and QoL was conducted. Physical performance was evaluated using the Timed Up and Go (TUG) test for balance, two dynamometers to measure handgrip strength and back-and-leg strength, and the Sit-and-Reach test to assess flexibility. Results. Significant improvements in physical health were demonstrated by the TUG test (p = 0.014) and Sit-and-Reach test (p = 0.035). In terms of QoL, notable gains were observed in the social relationship domain (p = 0.008) and overall QoL (p = 0.010). Conclusions. The present findings indicate that LRD has the potential to improve physical health and QoL among older adults. Overall, Thai cultural dance incorporating Ruesi Dadton represents a feasible and promising strategy for health promotion in this population. Further research, including long-term follow-up and randomized controlled trials, is warranted to confirm these preliminary results.